DRILL HOLE SPACING ANALYSIS USING GEOSTATISTIC METHODS FOR RESOURCES EVALUATION OF SEAM X IN PANEL Y ON KUTAI BASIN, TABANG DISTRICT, KUTAIKARTANEGARA REGENCY, EAST KALIMANTAN PROVINCE - Hidayat, Habil
Classification of resources based on the Indonesian National Standard (SNI) serves as a reference for classifying coal resources in Indonesia, taking into account the geological complexity and drilling geometry represented by borehole spacing. However, further studies are needed regarding the geological complexity in line with the advancement of geological knowledge in the mining exploration field, which can then be linked to coal quantity parameters such as layer thickness, as well as coal quality data including Calorific Value, Ash, Fixed Carbon, Inherent Moisture, Total Sulfur, and Volatile Matter. The average spacing of existing boreholes is a variable used in the analysis of borehole data distribution. The influence of geological complexity in the research area falls within the category of simple complexity and represents a measurable resource classification based on the resource classification obtained from existing borehole spacing. Global Estimation Variance (GEV) is the approach used in the analysis of borehole spacing to determine the optimal borehole spacing for Seam X. During estimation, a two-dimensional block approach is employed with block sizes of 100x100 m, 200x200 m, 300x300 m, 400x400 m, 500x500 m, 1000x1000 m, and 1500x1500 m. The results of GEV calculations are used to obtain relative error values, which are then adjusted according to the error classification: 0-10% for measured resources, 10-20% for indicated resources, and 20-50% for inferred resources. In the research area belonging to the Balikpapan Formation, the optimal borehole spacing results are 350 m for measured resources, 650 m for indicated resources, and 1400 m for inferred resources.